Energy aware cross layer-based connection admission control mechanism for wireless mesh networks. (2016) - Reddy, Pradeep; Krishna, P. Venkata
This paper studies the allocation scheme of bandwidth for the purpose of a quality end-to-end communication in multi-hop and multi-radio wireless mesh networks. In wireless mesh networks the role of bandwidth in providing QoS is pivotal. In view of the limited availability, efficient allocation of bandwidth becomes necessary. We proposed a scheme for connection admission control based on energy aware cross layer mechanism, to address the problems relating to the allocation of bandwidth for real-time and non-real-time traffic utilising a shared database. The shared database contains the energy available at the node, routing information, prediction of congestion and issues of congestion control in order to maximise the throughput of the network. The performance of the proposed model is evaluated in comparison with the other models utilising cross layer techniques. The design of the proposed network developed on the basis of energy aware cross layer optimisation, which yields considerable enhancement in the throughput of the network and these results can be crucial in the practical design of the network.